Guide to the Debt Management Performance Assessment Tool - World Bank (Washington, DC, 2013)
The purpose of this document is to provide guidance and supplemental information to assist with country assessments of debt management performance, using the Debt Management Performance Assessment (DeMPA) tool. The DeMPA is a methodology used for assessing public debt management performance through a comprehensive set of 15 performance indicators spanning the full range of government Debt Management (DeM) functions. It is based on the principles set out in the International Monetary Fund (IMF) and World Bank guidelines for public debt management, initially published in 2001 and updated in 2003. It is modeled after the Public Expenditure and Financial Accountability (PEFA) framework for performance measurement of public financial management. The DeMPA has been designed to be a user-friendly tool to undertake an assessment of the strengths and weaknesses in government DeM practices. This guide provides additional background and supporting information so that a no specialist in the area of debt management may undertake a country assessment effectively. The guide can be used by assessors in preparing for and undertaking an assessment. It is particularly useful for understanding the rationale for the inclusion of the indicators, the scoring methodology, and the list of supporting documents or evidence required, and the questions that could be asked for the assessment.